The Effect of Bay Leaf (Syzygium Polyanthum) Extract Hand Washing Liquid Soap Preparation on The Growth of Escherichia Coli Bacteria in Vitro - Wahdaniah; Asep Sabolakna; Bella Ramadhanti; Bagus Muhammad Ihsan; Yeremiah Rubin Tjamin (Jurnal Penelitian Pendidikan IPA, 2024)
Bay leaf (Syzygium polyanthum) is known as a complement to cooking spices, also used by the community for treatment. The content of antibacterial compounds from bay leaves such as alkaloids, flavonoids, saponins and tannins which can inhibit bacterial growth. This study aims to determine the effect of hand washing liquid soap with bay leaf extract on the growth of Escherichia coli bacteria. This study uses a Quasi Experiment research design. The population in this study is located on Jalan Atot Ahmad, West Pontianak District. The sample used was liquid hand washing soap with bay leaf extract at a concentration of 3, 6, and 9%, 9 repetitions with a total of 27 samples, using the disc diffusion method. The results of the antibacterial study showed that the average diameter of the inhibition zone at 3% concentration was 8.27 mm, 6% concentration was 10.55 mm and 9% concentration was 11.16. The results of the Linear Regression test using the Anova test obtained pvalue = 0.000, which is pvalue < α, with α = 0.05, so that it was stated that H1 was accepted so that there was an effect on the preparation of liquid hand washing soap (Syzygium polyanthum) extract on the growth of Escherichia coli bacteria in vitro.